Inverse Agonistic Activity of Antihistamines and Suppression of Histamine H1 Receptor Gene Expression - Hiroyuki Mizuguchi; Shohei Ono; Masashi Hattori; Hiroyuki Fukui (Elsevier, 2012)
Histamine H1 receptor (H1R) expression influences the severity of allergy symptoms. We examined the effect of inverse agonists on H1R gene expression. Two inverse agonists (carebastine and mepyramine), but not the neutral antagonist oxatomide, decreased inositol phosphate accumulation. The inverse agonists also decreased H1R gene expression and down-regulated H1R mRNA below basal expression, while basal H1R mRNA expression was maintained after oxatomide treatment. These results suggest that inverse agonists more potently alleviate allergy symptoms by not only inhibiting stimulus-induced up-regulation of H1R gene expression but also by suppressing basal histamine signaling through their inverse agonistic activity. Keywords:: constitutive activity, histamine H1 receptor gene transcription, inverse agonist